Impact of Teaching Style and Arm Muscle Strength on Bulletproof Learning Outcomes - Boby Helmi; Ramadan; Dicky Hendrawan (Jurnal Pendidikan Jasmani (JPJ), 2020)
The purpose of this study was to determine the effect of command and reciprocal teaching styles and arm muscle strength on learning outcomes of shot put. This research was conducted on students of SMP Negeri 2 Kuala Langkat, this study used treatment by level 2 x 2. The sample consisted of 44 students divided into four groups, each consisting of 11 pesilat. The data analysis technique is the analysis of two-lane variance (ANOVA) and then followed by the Tukey test at the significance level α = .05. The results of this study indicate that (1) 1. There are differences in learning outcomes of shot putting between reciprocal teaching styles and command teaching styles. (2) Learning Outcomes Shot of students with high arm muscle strength taught by using reciprocal teaching styles is no better than command teaching style. (3) Learning Outcomes Refuse bullets of students with low arm muscle strength taught by using the command teaching style is better than the reciprocal teaching style. (4) There is an interaction between the Learning Model and Arm Muscle Strength on Shot Ability.